A uremic toxin 3-carboxy-4-methyl-5-propyl-2-furanpropionate accumulates in proximal tubular cells and induces cell damage through increasing oxidative stress - Miyamoto, Y.; Iwao, Y.; Watanabe, H.; Kadowaki, D.; Ishima, Y.; Chuang, Victor; Sato, K.; Otagiri, M.; Maruyama, T. (Oxford University Press, 2012)
Introduction and Aims: 3-Carboxy-4-methyl-5-propyl-2-furanpropionate (CMPF) is a furan fatty acid derivative, a uremic toxin and a substrate of transporters for organic anions that contribute to the accumulation of CMPF in renal tubular cells. However, information regarding cytotoxicity of CMPF is limited. The purpose of this study was to develop the redox properties of CMPF and its association with renal cellular damage. Methods: Chemiluminescence was measured to investigate the interaction between CMPF and superoxide anion radicals (O2 •-) and peroxy radicals (LOO•). The effect of CMPF on the production of intracellular reactive oxygen species (ROS), cell viability and the secretion of the active transforming growth factor (TGF)-β1 were studied using human renal proximal tubular epithelial cells (HK-2 cells). Results: The present study showed that CMPF directly interacts with O2 •- and LOO• to produce CMPF radicals.The subsequent interaction of CMPF radicals with dissolved oxygen leads to the overproduction of O2 CMPF enhances the production of ROS in HK-2 cells in the presence of angiotensin II (A-II), an inducer of O2 When iron is present with CMPF and A-II, the Fenton reaction is induced, and a further increase in the ROS production was observed in HK- 2 cells. Such CMPF-induced oxidative stress increases the levels of active TGF-β1secretion in HK-2 cells. Interestingly, a positive correlation between CMPF-induced ROS production and the secretion of active TGF-β1 was observed. CMPF caused a reduction in cell viability which was negatively correlated with intracellular ROS production. These deteriorative effects of CMPF in HK-2 cells were completely suppressed by probenecid, an inhibitor of the transport of organic anions. Conclusions: CMPF, which accumulates in the renal cells, appears to play a prominent role as a pro-oxidant which subsequently leads to renal cellular damage via the overproduction of O2 •-